أبعاد الجغرافية الاقتصادية للعلاقات الدولية: دراسة في التأثيرات المتبادلة والتحديات المعاصرة (Comprehensive Journal of Science, 2025)
This study examined the economic-geographical dimensions of international relations by investigating the mutual influences between geographical factors and economic and political interactions among nations, as well as analyzing the challenges arising from these interactions in the context of contemporary global issues. The significance of this research lies in its attempt to provide a deeper understanding of how economic-geographical determinants interact with political, security, and cultural variables in shaping international relations. The study adopts a multidimensional approach that transcends traditional boundaries between disciplines and accommodates the increasing complexities and interconnectedness within the international system. The research reviewed relevant Arabic and foreign previous studies that addressed various aspects of the interaction between geography, economy, and politics in international relations, such as geostrategic competition among powers, regional systems, transformations in prevailing theories, geographical economics, and knowledge economy. The research presented a theoretical and conceptual framework for analyzing the economic-geographical dimensions, drawing upon the realist theory in international relations and the field of international political economy. It highlights the challenges facing international relations as a result of the economic-geographical impacts of pressing global issues, such as climate change, pandemics, and regional conflicts, and their effects on resources, infrastructure, and competition among powers. The study concluded the necessity of adopting a comprehensive perspective to understand the interaction of economic-geographical factors with political, security, and cultural variables. Recommendations were proposed to enhance international cooperation in addressing common challenges, taking into account the multiple dimensions of international relations amidst the changes in the contemporary global political economy.
Keywords: Economic-geographical, International relations, Global economy,Geo-Economics